A history of christianity : the first three thousand years - MacCulloch, Diarmaid (London, UK : Penguin Books, 2009)
Christianity, one of the worlds great religions, has had an incalculable impact on human history. This book, now the most comprehensive and up to date single volume work in English, describes not only the main ideas and personalities of Christian history, its organisation and spirituality, but how it has changed politics, sex, and human society.Diarmaid MacCulloch ranges from Palestine in the first century to India in the third, from Damascus to China in the seventh century and from San Francisc.
Greece and Rome (c. 1000 BCE - 100 CE) -- Israel (c. 1000 BCE-100 CE) -- A crucified Messiah (4 BCE-100 CE) -- Boundaries defined (50 CE-300) -- The prince : ally or enemy (100 - 300) -- The imperial Church (300-451) -- Defying Chalcedon : Asia and Africa (451-22) -- Islam : the great realignment (622-1500) -- The making of Latin Christianity (300-500) -- Latin Christendom : new frontiers (500-1000) -- The West : universal emperor or universal pope? (900-1200) -- A church for all people? ( 1100-1300) -- Faith in a new Rome (451-900) -- Orthodoxy : more than an empire (900-1700) -- Russia : the third Rome (900-1800) -- Perspectives on the true church (1300-1517) -- A house divided (1517-1660) -- Rome's renewal (1500-1700) -- A worldwide faith (1500-1800) -- Protestant awakenings (1600-1800) -- Enlightenment : ally or enemy (1492-1815) -- Europe re-enchanted or disenchanted (1815-1914) -- To make the world Protestant (1700-1914) -- Not peace but a sword (1914-60) -- Culture wars (1960- present).
Includes bibliographical references and index.
Keywords: Church history